(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The physical fitness of young people, particularly those pursuing a degree in Physical Education and Sport, is a multifaceted phenomenon that encompasses the development of strength, endurance, speed, agility, flexibility, coordination, motor memory, and recovery capacity. An adequate level of these attributes is essential for the effective professional performance of coaches, educators, and physical activity organizers. The purpose of this study is to characterize the physical fitness level of future specialists in physical education and sport at the initial (ascertaining) stage of the research, identify key problematic aspects, and justify the need for the integration of innovative physical training programs into the educational process. The analysis revealed that most students demonstrated below-norm physical fitness indicators. Among female students, the highest results were observed only in speed tests (100-meter sprint and 4×9 m shuttle run), where 6.66% achieved an “excellent” rating, 86.68% – “good,” and 6.66% – “satisfactory,” indicating a predominantly average level of speed development. In the standing long jump, only 6.66% achieved excellent results, 63% – good, and over 30% – satisfactory, suggesting insufficient development of speed-strength abilities. The lowest performance was recorded in endurance tests, flexibility assessments, and tests of muscular endurance of the trunk and upper limbs. Male students also exhibited insufficient levels of endurance, flexibility, and upper body strength. Although they performed better in speed and agility tests, the proportion of those who achieved an “excellent” rating remained low. Overall, the integral assessment of physical fitness among both male and female students was below average, indicating limited functional reserves of the body.